Teachers' Beliefs About Integrating Digital Literacy Into Classroom Practice: An Investigation Based on the Theory of Planned Behavior. Issue 4 (2nd October 2017) - Sadaf, Ayesha; Johnson, Barbara L.
Abstract: This study explored teachers' behavioral, normative, and control beliefs related to digital literacy integration into their classrooms. Ajzen's Theory of Planned Behavior (TPB) was used as a theoretical framework to collect and analyze data. Findings revealed that teachers' integration of digital literacy were related to their behavioral beliefs (attitude toward outcomes of a behavior) about the value of digital literacy for developing students' 21st-century skills, increasing student engagement, and preparation for future careers; normative beliefs (social support) about meeting the expectations of administrators, parents, colleagues, and students; and control beliefs (perceived behavioral control) about ease of integrating digital literacy due to access to technology, professional development, and curriculum resources.